Digital for real: A multicase study on the digital transformation of companies in the embedded systems domain. Issue 5 (1st February 2021) - Bosch, Jan; Olsson, Helena H.
Abstract: With digitalization and with technologies such as software, data, and artificial intelligence, companies in the embedded systems domain are experiencing a rapid transformation of their conventional businesses. While the physical products and associated product sales provide the core revenue, these are increasingly being complemented with service offerings, new data‐driven services, and digital products that allow for continuous value creation and delivery to customers. However, although there is significant research on digitalization and digital transformation, few studies highlight the specific needs of embedded systems companies and what it takes to transform from a traditional towards a digital company within business domains characterized by high complexity, hardware dependencies, and safety‐critical system functionality. In this paper, we capture the difference between what constitutes a traditional and a digital company and we detail the typical evolution path embedded systems companies take when transitioning towards becoming digital companies. Abstract : The four dimensions of successful digital transformation are the product upgrade dimension, the business model dimension, the data exploitation dimension, and the AI/ML/DL dimension.